Evaluation of HSP-27, BAP1, BRAF V600E, CCR7, and PD-L1 expression in uveal melanoma on enucleated eyes and metastatic liver tumors. Issue 2 (June 2022) - Ağın, Abdullah; Kiratli, Hayyam; Guresci, Servet; Babaoglu, Berrin; Karakaya, Jale; Soylemezoglu, Figen
Background: The presence of metastatic disease is one of the most important factors limiting survival in patients with uveal melanoma. Studies on proteins associated with metastatic mechanisms are sparse in the literature. Methods: Enucleation samples from 15 patients with metastatic uveal melanoma (Group 1), liver metastasectomy samples from 8 patients with metastatic uveal melanoma (Group 2), and enucleation samples from 20 patients with non-metastatic uveal melanoma as controls (Group 3) were included in the study. Antibodies against heat shock protein 27 (HSP-27), BRCA1-associated protein-1 (BAP1), C-C chemokine receptor 7 (CCR7), B-Raf proto-oncogene serine/threonine-protein kinase V600E (BRAF V600E), and programmed death-ligand 1 (PD-L1) were used to detect immunoreactivity in each sample by immunohistochemical methods. Correlations between these expressed proteins and selected histopathological and clinical features, and metastatic process were investigated. Results: The frequencies of HSP-27 (median score: Group 1: 8, Group 2: 12, Group 3: 4) and BRAF V600E expressions (number of samples: Group 1: 4 (26.7%), Group 2: 1 (12.5%), Group 3: 0 (0%)), and BAP1 expression loss (number of samples : Group 1: 12 (80%), Group 2: 8 (100%), Group 3: 9 (45%)) were higher in samples from patients with metastatic uveal melanoma (Group 1 + 2) than in those from patients with non-metastatic disease (Group 3) ( P  = 0.001, P  = 0.034, and P  = 0.007, respectively). CCR7 expression (median score: Group 1: 0, Group 2: 2, Group 3: 3) was similar among these three groups ( P  = 0.136). No samples exhibited PD-L1 expression ( P  = 1.000). One-unit increases in the HSP-27 expression level and BAP1 expression loss were significantly related to 1.375- and 7.855-fold increases in the risk of metastasis, respectively ( P  = 0.007 and P  = 0.017). Conclusion: HSP-27 and BAP1 are considered to be associated with metastasis, indicating these proteins as potential treatment targets in metastatic uveal melanoma.